Pemahaman Teknologi Modern Dalam Perlindungan Tanaman Pangan Dan Produktivitas Maksimal - Nasution, Susan Tri Susanti Rahmadhani; Telaumbanua, Miskaria Murni; Lase, Ningsi Kristiani; Mendrofa, Makchsi Virall; Dawolo, Toni Yusman; Zebua, Helmin Parida (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Modern technologies play a vital role in supporting crop protection and maximizing productivity. The study explores various cutting-edge technologies, such as sensor-based systems, drones, and biological pest control, to manage biotic and abiotic stresses on crops. The study also highlights the use of genomics and genetic engineering to develop crop varieties that are resistant to pests and diseases. The results show that these technologies not only improve crop protection efficiency but also reduce dependence on hazardous chemicals, supporting the sustainability of agricultural ecosystems. In addition, the integration of blockchain technology in the supply chain ensures transparency and food safety. The study concludes that the right understanding and application of modern technologies can significantly boost crop productivity growth, while addressing the global challenge of meeting the ever-increasing food demand.